The ergonomics edge improving safety, quality, and productivity - MacLeod, Dan (Van Nostrand Reinhold, 1994)
In The Ergonomics Edge, Dan MacLeod demonstrates why ergonomics is really good news for managers, revealing how it can actually be a formidable weapon in a company's quest to gain competitive advantage. MacLeod is one of the leading practitioners of workplace ergonomics in the U.S., and has successfully applied ergonomics in many manufacturing and service industries. He shows how improving the user-friendliness of both the workplace and a company's end-product can lead to reduced workers' comp, turnover, absenteeism, and other cost savings. Moreover, he reveals how ergonomics can lead to higher earnings through greater worker productivity and increased sales. Highly illustrated and written in a conversational style, The Ergonomics Edge provides a non-technical approach designed to demystify this subject that many find daunting. The Ergonomics Edge is the first working resource to offer convincing evidence that ergonomics can be a blessing and not a burden to U.S. business.This book will be indispensable in helping your firm meet its long-range strategic goals. In addition, it will be important reading for ergonomists, industrial hygienists, physical therapists. and other safety and medical professionals, to help everyone make the case for ergonomics.